Uniform wet-Spinning Mechanically Automated (USMA) fiber device. (October 2020) - Mitropoulos, Alexander N.; Kiesewetter, Kylor T.; Horne, Eric; Butler, Jeff; Loverde, Joseph R.; Wickiser, J. Kenneth
Graphical abstract: Abstract: Bioengineering techniques for producing fibers from biomaterials is a growing requirement in medical device technology research and development environments. Scale-up and control of diameter, shape, and length of fibrous proteins and elastomeric polymers are essential to produce defined and consistent materials for experimentation and clinical use. Here, we developed a novel wet spinning fiber extruder and spooler system engineered to draw precipitated fibers several meters in length across five spools. By controlling both the extrusion and spooling rate, the diameter of the fiber can be controlled on the order of 10–1000 µm. Using this system, we extruded and spooled precipitated Type-1 Collagen fibers up to 7.5 m in length on a single spool with a controllable diameter range of 30–50 µm. Furthermore, this device facilitated bundling of fibers directly on the spool in order to create 1–12 cm long fiber bundles for experimentation. This system may be used in the laboratory to scale up biomaterial fiber production to produce degradable scaffolds made from synthetic or natural materials for a range of biomedical applications.